Analysis of Schlemm’s canal measurement and evaluation with fourier-domain optical coherence tomography in Primary Open-Angle Glaucoma - Sucijanti,; Yuan, Zhi Lan; Liang, Ya; Hong, Sun; Gu, Liu Wei; Zhenli, Si (Penerbit Universiti Kebangsaan Malaysia, 2024)
The most common cause of permanent vision loss or blindness in the world is glaucoma. Primary Open Angle Glaucoma (POAG) develops when the eye drainage canals clog over time, increasing intraocular pressure and damaging the optic nerve. In POAG, an ophthalmology examination usually shows an open anterior chamber and chronic, irreversible multifactorial optic neuropathy followed by central visual field loss. OCT is specifically employed to investigate the elasticity of tissue, particularly in Schlemm’s canal. This study aims to analyzed the morphological parameters of Schlemm’s canal among patients with POAG and normal healthy control. In this observational study, we included one hundred patients, among them 50 patients had POAG, and 50 healthy controls, and both eyes were assessed. We measured the study cohort’s and the healthy cohort’s eyes’ elevated IOP and the Schlemm’s canal cross-sectional area (CSA). RT-Vue OCT was used to analyze both eyes’ temporal, superior, inferior, and nasal regions. The data were analyzed using both univariate and bivariate methods. The characteristics of the morphological measurement of Schlemm’s canal results were similar to those of Kagemann et al. There was a significant difference between age and SC measurement, but no correlation was observed between SC measurement and IOP or visual acuity. OCT is a useful way to evaluate the morphological status of Schlemm Canal in glaucoma patients. The eyes with POAG had smaller Schlemm’s Canal- CSA than the normal eyes. The Schlemm canal-CSA in Chinese people had no differences from that of peoples of other races.